Точка падения: [фантастический роман] / Юрий Бурносов - Бурносов Юрий Николаевич (S.T.A.L.K.E.R., 2011)
Экземпляры: аб. (20180412) / Инвентарный номер: 58238 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: Б 91 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-445